2020
DOI: 10.1016/j.jhep.2019.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity compared to adiposity and risk of liver-related mortality: Results from two prospective, nationwide cohorts

Abstract: Highlights Low physical activity and obesity predicted an excess risk of liver-related death. The excess risk conferred by obesity was markedly attenuated by physical activity. Overall, walking for >3 hours/week could have prevented 25% of liver-related deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 53 publications
1
20
0
2
Order By: Relevance
“…Several reports have stressed the prognostic significance of eGFR in CLD patients, which were in agreement with our results (42)(43)(44). While, BMI and WC (adiposity-related markers) were not associated with the OS in our study, although a recent large prospective cohort study demonstrated the prognostic significance of excess adiposity (45). The reason for these discrepancies between studies remains unclear.…”
Section: Discussionsupporting
confidence: 89%
“…Several reports have stressed the prognostic significance of eGFR in CLD patients, which were in agreement with our results (42)(43)(44). While, BMI and WC (adiposity-related markers) were not associated with the OS in our study, although a recent large prospective cohort study demonstrated the prognostic significance of excess adiposity (45). The reason for these discrepancies between studies remains unclear.…”
Section: Discussionsupporting
confidence: 89%
“…Our study demonstrates that physical activity is not only associated with reduced liver disease progression, but also linked to reduced liver disease development. Several studies have focused on the role of physical activity in NAFLD, while data on other liver diseases is limited[16]. Our findings suggest…”
mentioning
confidence: 54%
“…Studies have reported that reduced PA were positively associated with the prevalence of NAFLD and liver-related mortality. 14,15 In contrast, vigorous-intensity PA reduces the severity of NAFLD. 16 Although the association between lifestyle habits and NAFLD has been well studied, clinicians and policymakers need to identify areas of deficiency so as to prevent and manage NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…However, physical inactivity has become a serious public health problem for patients with chronic liver diseases. Studies have reported that reduced PA were positively associated with the prevalence of NAFLD and liver‐related mortality 14,15 . In contrast, vigorous‐intensity PA reduces the severity of NAFLD 16 …”
Section: Introductionmentioning
confidence: 99%